Extinction of conditioned eyelid responses requires the anterior lobe of cerebellar cortex - Perrett, SP (J Neurosci, 1995)
We test the hypothesis that the cerebellar cortex is required for the extinction of conditioned eyelid responses in rabbits trained using standard Pavlovian delay procedures. Following 10 daily training sessions during which rabbits achieved asymptotic performance, lesions of the ipsilateral hemisphere of the cerebellar cortex were made by aspiration. The target of these lesions was the anterior lobe, as suggested by previous observations that this region is necessary for the learning-dependent timing of conditioned eyelid responses (Perrett et al., 1993). We report that anterior lobe damage, as indicated by disrupted response timing and confirmed by tissue analysis, produces severe deficits in conditioned response extinction. Postlesion responses show no significant decline over ten training sessions, whereas response timing and extinction are unaffected by lesions that do not include the anterior lobe. These conditioned responses that do not extinguish display stimulus specificity, excluding the possibility that they are unlearned responses unmasked by cerebellar cortex lesions. These observations suggest that Pavlovian eyelid conditioning is mediated by synaptic plasticity in at least two sites and the anterior lobe of the cerebellar cortex influences one of these sites during extinction. Based on these and previous data, we propose the hypothesis that eyelid conditioning can involve plasticity in both the cerebellar cortex and interpositus nucleus and that plasticity in the nucleus is controlled by input from Purkinje cell activity in the cortex. This hypothesis is consistent with observations that the cerebellar cortex may not always be required for the expression of conditioned responses, but it is necessary for response timing and for extinction.